Pengaruh Kecukupan Modal, Pembiayaan Bermasalah, Efisiensi Operasional, dan Tingkat Likuiditas Terhadap Profitabilitas Pada Bank BTPN Syariah Periode 2014-2019 - Eka Darmayani (Pt. Anagata Sembagi Education, 2024)
This study aims to determine the effect of capital adequacy, problem financing, operational efficiency, and liquidity level on the profitability of BTPN Syariah for the 2014-2019 period. The research method used in this research is descriptive quantitative, with the object of research capital adequacy proxied Capital Adequacy Ratio (CAR), financing problems proxied Non Performing Financing (NPF), Operational Efficiency proxied Operational Expenses Operating Income (BOPO), liquidity level proxied Financing to Deposit Ratio (FDR) and profitability are proxied by Return On Assets (ROA). As the research subject is the annual financial report (Annual Report) from the BTPN Syariah quarter 2014-2019. Methods of data analysis using multiple linear regression.The results showed that the significant value of CAR of 0.000 <0.05 has a significant effect on ROA, a significant value or NPF of 0.000 <0.050 has a significant effect on ROA, a significant value or BOPO of 0.010 has a significant effect on ROA, and a significant value of FDR of 0.050 is equal to 0.050 has a significant effect on ROA. The results of the analysis show that CAR and BOPO have a positive effect on ROA, while NPF and FDR have a negative effect on ROA. From this study, the CAR value is a variable that has a strong influence on ROA.